RANCANG BANGUN GAME HIRAKANA HEROES BERBASIS WEB - Tri Herdiawan Apandi; Risky Prabowo (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
The development of Japanese interest in Indonesian society increases every year from 2006 as many as 207,000 people learn Japanese more than tripled in 2009 to 720,000 people and in 2012 there were 872,406 Indonesians studying Japanese. With the increasing interest of the Indonesian people towards Japanese, some institutions have some problems where as much as 61.4% stated lack of information on teaching materials and teaching methods and 41% stated lack of teaching materials. The author tries to create a game that teaches the letters Hiragana and Katakana through game media to create interactive media and facilitate the learning process. From the result of user acceptance test (UAT) got the result of 92,4% so it can be concluded that game hirakana heroes together kiky the kancil can add learning media and facilitate learning letters Hiragana and Katakana. Keywords: Game, Hiragana, Japan, Katakana